A model of madrasa ibtidaiya quality evaluation - Dwi Istiyani; Zamroni Zamroni; Suharsimi Arikunto (Universitas Negeri Yogyakarta, 2017)
The study was to develop a madrasa ibtidaiya quality evaluation model (MIQEM) for measuring the quality of madrasa ibtidaiya (MI), including the input, the process, the short-term outcome, and the long-term outcome. The method implemented in this research was research and development (R & D). The subjects of the study were the principals and teachers of state madrasa ibtidaiya. The study concluded that: (1) the a MIQEM was developed through the product selection, review and result analysis, and model draft; (2) the implementation of the developed MIQEM was done by the principals and the teachers by operating the MIQEM instrument; (3) the results of the developed MIQEM implementation showed that it could improve madrasa ibtidaiya quality; (4) the results of the model fitness test indicated that the model was fit into the data.